Global language geography and language history: challenges and opportunities [version 2; peer review: 1 approved, 3 approved with reservations] - Matthias Urban (Open Research Europe)
While it has almost become a truism of comparative linguistics that linguistic diversity is unevently distributed across the globe, the reasons are poorly understood up to the present day. Linguists are thus in the embarassing situation that they do not understand significant regularities in the way the objects of their study –languages– pattern. In this essay, I explore three interrelated strands of thought to create a perspective on the question that is different from those explored so far: first, I suggest that instead of looking at present-day levels of diversity statically, we should take an approach that looks into how these distributions were generated. Related to this point and in contradistinction to extant work, second, I advocate an inductive approach that departs from qualitative case studies that inform theory-building. Third, I ponder that, in contrast to the traditional focus of historical linguistics on language diversification and expansion, understanding how the ranges of languages are reduced might be the key missing piece of evidence in a global theory of language diversity and its genesis. This new perspective is also able to address the striking correlation between linguistic and biological diversity that suggest that the processes that created and maintain both are, on some level, qualitatively similar.